Bark depolymerization during submerged fermentation using monofloral honey, a natural mediator substitute, and integration between laccases vs. bark biopolymers, characterized by Py-GC-MS. Issue 20 (6th March 2015) - Ferhan, M.; Yan, N.; Sain, M.
<x xml:space="preserve">Abstract</x> This is a new green biochemical approach to edify that how we can replace synthetic, toxic and costly mediators into natural mediator using monofloral honey which accelerates oxidation mechanism with combination of fungal laccases.